Fischer Black and the Revolutionary Idea of Finance - Mehrling, Perry (Hoboken John Wiley, 2012)
B The definitive story of Fischer Black, one of the greatest financial minds of all time/b Besides revolutionizing finance with the Black-Scholes option pricing model, Fischer Black forever changed Wall Street by developing what is now known as quantitative finance.
Include Index, Appendix and Notes
Keywords: United States -- Economists -- Finance